The relationship of accreditation and student engagement in a college of business: An internal, multi-year comparison of high impact practices. Issue 1 (March 2018) - Berry, Alison; Hammer, Emily
Abstract: This study examines a college of business at a regional university, according to High Impact Practices on the National Survey of Student Engagement as compared to student engagement at the regional university as a whole. Seven years of data across five High Impact Practices for both the college of business as well as its greater regional university were examined using a two-proportion z-test. The study concluded that the college of business was more stable than the greater university across four of the High Impact Practices. This study reveals that a college of business may function as an independent entity from its greater university concerning High Impact Practice participation which may be contextualized by the accreditation process. Specifically, the unique attributes of programmatic accreditation, as opposed to the institutional accreditation that all colleges and programs within a university must satisfy, may change behaviors related to student engagement. Highlights: The university outperformed its college of business in internships, learning communities, and research with faculty. The college of business typically outperformed its university in study abroad and a culminating senior experience. The college of business's senior engagement functioned independently from the greater university. The attributes of programmatic accreditation, as opposed to institutional accreditation, may influence student engagement.